Strategies to enhance drug delivery to solid tumors by harnessing the EPR effects and alternative targeting mechanisms - Zi, Yixuan; Yang, Kaiyun; He, Jianhua; Wu, Zimei; Liu, Jianping; Zhang, Wenli (Advanced drug delivery reviews, 2022)
[Display omitted] The Enhanced Permeability and Retention (EPR) effect has been recognized as the central paradigm in tumor-targeted delivery in the last decades. In the wake of this concept, nanotechnologies have reached phenomenal levels in research. However, clinical tumors display a poor manifestation of EPR effect. Factors including tumor heterogeneity, complicating tumor microenvironment, and discrepancies between laboratory models and human tumors largely contribute to poor efficiency in tumor-targeted delivery and therapeutic failure in clinical translation. In this article, approaches for evaluation of EPR effect in human tumor were overviewed as guidance to employ EPR effect for cancer treatment. Strategies to augment EPR-mediated tumoral delivery are discussed in different dimensions including enhancement of vascular permeability, depletion of tumor extracellular matrix and optimization of nanoparticle design. Besides, the recent development in alternative tumor-targeted delivery mechanisms are highlighted including transendothelial pathway, endogenous cell carriers and non-immunogenic bacteria-mediated delivery. In addition, the emerging preclinical models better reflect human tumors are introduced. Finally, more rational applications of EPR effect in other disease and field are proposed. This article elaborates on fundamental reasons for the gaps between theoretical expectation and clinical outcomes, attempting to provide some perspective directions for future development of cancer nanomedicines in this still evolving landscape.